Efficacy of flossing and mouth rinsing regimens on plaque and gingivitis: a randomized clinical trial - Mary Lynn Bosma; James A. McGuire; Alicia DelSasso; Jeffery Milleman; Kimberly Milleman (BMC, 2024)
Abstract Background To investigate the effects of combinations of mechanical (brushing and flossing) and chemotherapeutic regimens which included essential oils (EO) non-alcohol and alcohol-containing mouthrinses compared to brushing only in the prevention and reduction of plaque, gingivitis, and gingival bleeding. Methods This was a randomized, virtually supervised, examiner blind, controlled clinical trial. Following informed consent and screening, subjects (N = 270) with gingivitis were randomly assigned to one of the following regimens: (1) Brush Only (B, n = 54); (2) Brush/Rinse (EO alcohol-containing mouthrinse) (BA, n = 54); (3) Brush/Rinse (EO non-alcohol containing mouthrinse) (BZ, n = 54); (4) Brush/Floss (BF, n = 54); (5) Brush/Floss/Rinse (EO non-alcohol containing mouthrinse) (BFZ, n = 54). Unflavored waxed dental floss (REACH unflavored waxed dental floss), and fluoridated toothpaste (Colgate Cavity Protection) were used. Examinations included oral hard and soft tissue, plaque, gingivitis, gingival bleeding, probing depth and bleeding on probing. Results After 12 weeks, both BA and BZ and the BFZ group were superior in reducing interproximal plaque (30.8%, 18.2%, 16.0%, respectively), gingivitis (39.0%, 36.9%, 36.1%, respectively), and bleeding (67.8%, 73.6%, 79.8%, respectively) compared to B. The BF group did not provide significant reductions in interproximal plaque but did reduce interproximal gingivitis (5.1%, p = 0.041) at Week 4 and bleeding at Weeks 4 and 12 (34.6%, 31.4%, p < 0.001 respectively) compared to B. The BFZ group did not significantly reduce interproximal plaque, gingivitis or bleeding compared to BZ. Conclusions This study demonstrated that the addition of EO non-alcohol containing mouthrinse to the manual toothbrushing and flossing regimen further reduces plaque, gingivitis and bleeding showing that addition of EO mouthrinses (alcohol or non-alcohol containing) to the oral hygiene regimen provides sustained reductions in plaque to help maintain gingival health after a dental prophylaxis. Dental professional recommendation of the addition of an EO non-alcohol containing mouthrinse to daily oral hygiene routines of brushing or brushing and flossing should be considered to aid supragingival plaque control and improve gingivitis prevention. Study registry number NCT05600231.